Understanding Flipping Behaviour of Crude Oil Prices between Contango and Backwardation - Hassan, Abubakar (University of Dundee, 2022)
The last four decades have witnessed extraordinary volatility in crude oil prices, and this has severe implications for the race toward achieving a net-zero carbon emission target by 2050. This thesis attempts to understand the dynamic behaviour of crude oil prices through four interrelated essays on the flipping behaviour of crude oil prices between contango and backwardation market conditions. The thesis revealed interesting findings by employing robust econometric estimation techniques and innovative ideas on weekly and monthly Brent and WTI spot and futures prices spanning from January 1986 to April 2021. The first research essay reveals that price discovery takes place in Brent spot and WTI futures markets, and volatility spillovers from spot to futures market in the Brent market whereas, in the WTI market, volatility spillovers from futures to spot market. The second essay reveals that WTI stays longer in the backwardation market state, but the contango market state has a more profound impact on the crude oil market. The third essay reveals that six major oil price structural breaks significantly impact the contango and backwardation market conditions. The essay also shows that on April 20, 2020, the oil price shock flipped the oil market from backwardation to contango. Finally, the fourth essay reveals that convenience yield and inventory have a significant asymmetric nonlinear impact on crude oil prices, in line with the central prediction of the theory of storage. Overall, the thesis has four main contributions. First, it is the first research work to systematically explore the theory and evidence of the flipping behaviour of crude oil prices between contango and backwardation. Second, it is one of the pioneering research works in using Markov Regime-switching models and in harvesting the information content of crude oil futures curves. Third, it is also the first research work to analyse the impact of oil price structural breaks on contango and backwardation market states. Finally, the thesis uses econometric estimation techniques to bridge existing research voids on price discovery, volatility spillovers, and lead-lag relationships in Brent and WTI crude oil markets.